Adherence to Endotracheal Tube Depth Guidelines and Incidence of Malposition in Infants and Children - Volsko, Teresa A; McNinch, Neil L; Prough, Donald S; Bigham, Michael T (Respiratory care, 2018)
Adherence to guidelines for endotracheal tube (ETT) insertion depth may not be sufficient to prevent malposition or harm to the patient. To obtain an estimate of ETT malpositioning, we evaluated initial postintubation chest radiographs and hypothesized that many ETTs in multiple intubation settings would be malpositioned despite adherence to Pediatric Advanced Life Support and Neonatal Resuscitation Program guidelines. In a random subset (randomization table) of 2,000 initial chest radiographs obtained from January 1, 2009, to May 5, 2012, we recorded height, weight, age, sex, ETT inner diameter, and cm marking at the lip from the electronic health record. Chest radiographs of poor quality and with spinal or skeletal deformities were excluded. We defined adherence to Pediatric Advanced Life Support or Neonatal Resuscitation Program guidelines as the difference between predicted and actual ETT markings at the lip as ± 0.25, ± 0.50, or ± 1.0 cm for ETTs of 2.5-4, 4.5-6.0, or >6.5 mm inner diameter, respectively. We defined the proper position as the ETT tip being below the thoracic inlet (superior border of the clavicular heads) and ≥1 cm above the carina. Descriptive statistics reported demographics, guideline adherence, and malposition incidence. The chi-square test was used to assess relationships among intubation setting, malposition, and depth guideline adherence ( < .05, significant). We reviewed 507 records, 477 of which met inclusion criteria and had sufficient data for analysis. Fifty-six percent of the subjects were male, with median (interquartile range) age 15.2 (3.4-59.4) months, and 330 ETTs (69%) were malpositioned: 39 above the thoracic inlet, and 291 < 1 cm above the carina. Of 79 ETTS (17%) that adhered to depth guidelines, 56 (74%) were malpositioned. Three-hundred seventy-three ETTs (83%) did not meet guidelines. Two-hundred sixty-four (68%) were malpositioned. The intubation setting did not influence malposition or guideline adherence ( = .54). In infants and children, a high proportion of ETTs were malpositioned on the first postintubation chest radiograph, with little influence of guideline adherence.